(untitled) (Research, Society and Development, 2022)
Obesity is the accumulation of excess adipose tissue that affects a person’s health and physical and psychosocial well-being. The classification is based on the body mass index, which makes it possible to compare prevalence rates worldwide. Obesity and overweight have become a global epidemic in both developed and developing countries. The objective of this study is to assess the prevalence of obesity and overweight in some countries. The results showed that in the last two decades, the prevalence of obesity and overweight in the world has more than doubled. The predominance of obesity and overweight is more pronounced in Western and Westernized countries, which are more developed, than in developing countries where malnutrition and obesity coexist. This global epidemic is seen in adults, adolescents and children without exception of gender. Obesity and overweight are one of the main factors in the increase of non-communicable diseases such as cardiovascular diseases, diabetes, musculoskeletal disorders and some types of cancer in the world. Poor diet is the main cause of the growing prevalence of obesity.